2019
DOI: 10.1002/mdc3.12769
|View full text |Cite
|
Sign up to set email alerts
|

A Severe l‐Dopa Responsive Dystonia With Slow and Continuous Improvement in a Patient With a Novel Mutation in the Tyrosine Hydroxylase Gene

Abstract: View Supplementary Video 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
(10 reference statements)
0
1
0
1
Order By: Relevance
“…We compiled the summary from Dong et al, encompassing all TH deficiency cases reported through 2018 (Dong et al, 2020) and all Segawa patients published thereafter until 2023 (Atanasoska et al, 2023; Bijarnia‐Mahay et al, 2020; Champagne et al, 2022; Chen et al, 2020; Couto et al, 2019; Hou et al, 2019; Hull et al, 2021; Janssen et al, 2021; Kuseyri Hubschmann et al, 2021; Panda et al, 2022; Reyes et al, 2023; Wang et al, 2022). In total, we summarized the clinical phenotypes of all 175 reported Segawa cases.…”
Section: Case Presentationmentioning
confidence: 99%
“…We compiled the summary from Dong et al, encompassing all TH deficiency cases reported through 2018 (Dong et al, 2020) and all Segawa patients published thereafter until 2023 (Atanasoska et al, 2023; Bijarnia‐Mahay et al, 2020; Champagne et al, 2022; Chen et al, 2020; Couto et al, 2019; Hou et al, 2019; Hull et al, 2021; Janssen et al, 2021; Kuseyri Hubschmann et al, 2021; Panda et al, 2022; Reyes et al, 2023; Wang et al, 2022). In total, we summarized the clinical phenotypes of all 175 reported Segawa cases.…”
Section: Case Presentationmentioning
confidence: 99%
“…llegando a describirse en dos casos, una demora de aproximadamente 20 años entre el inicio de síntomas y el diagnóstico (9,11). El compromiso inicial de una extremidad, específicamente miembro inferior, ha sido descrito como parte de la forma clásica de DRD, así como las fluctuaciones diurnas.…”
Section: Si Gch1unclassified